Studi Literatur: Pengetahuan sebagai Salah Satu Faktor Utama Pencegahan Penularan COVID-19 - Abdul Ganing; Andi Salim; Irma Muslimin (Politeknik Kesehatan Kemenkes Mamuju, 2020)
Current conditions show that the coronavirus is not an epidemic that can be ignored. When viewed from the symptoms, ordinary people would think that it was only common influenza, but for medical analysis, this virus is quite dangerous and deadly. Currently, the effort that can be done to avoid the transmission of Covid-19 is to take preventive measures as early as possible. This article aims to review the extent of knowledge of Literature Review by reviewing five papers from the Science Direct and Google Scholar databases. The results showed that the five articles reviewed showed that students, health workers, and the general public gained independent knowledge about Covid-19 in different ways. The knowledge is formed from information obtained from the internet and social media, TV, newspapers/magazines, discussions with peers, and from lessons learned in college. Therefore, the government should pay attention to the dissemination of information related to Covid-19 so that the public can receive accurate information as an effort to form knowledge so that accurate preventive measures can be obtained against Covid-19 in the community.